2002
DOI: 10.1248/bpb.25.193
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by Dioscin in Hela Cells.

Abstract: Dioscin, a saponin extracted from the root of Polygonatum Zanlanscianense Pamp, markedly inhibited proliferation of Hela cells. The results indicated that Hela cells underwent apoptosis in dose-and time-dependent manners when treated with Dioscin. Caspase-3, -8 and -9 activities were also detected. The low enzymatic activity of caspase-8 and high activity of caspase-9 showed that the mitochondrial pathway was activated in apoptosis. The reduced expression of the survival protein Bcl-2 also confirmed this resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 14 publications
3
50
0
Order By: Relevance
“…8,9) Recent studies have shown that they have cytotoxic properties against several strains of human cancer cells. [10][11][12][13][14] Dioscin [15][16][17] and trillin 18) are the best known diosgenyl saponins with these properties (Fig. 1).…”
mentioning
confidence: 99%
“…8,9) Recent studies have shown that they have cytotoxic properties against several strains of human cancer cells. [10][11][12][13][14] Dioscin [15][16][17] and trillin 18) are the best known diosgenyl saponins with these properties (Fig. 1).…”
mentioning
confidence: 99%
“…Dioscin (Cai et al, 2002;Zhang et al, 2006;Wang et al, 2007a;Yun et al, 2007;Nguyen et al, 2009), one of the components of RPS, is a preclinical drug showing potent antiproliferative activities against most cell lines from leukemia and solid tumors. In cell culture experiments with HeLa cervix carcinoma cells, it could dose-and time-dependently induce apoptosis via the mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Yam exhibits several useful biological properties, such as antioxidative (Hou et al, 2001(Hou et al, , 2002, cholesterol-lowering , and anticholinesterase (Oh et al, 2004) effects, as well as anti-inflammatory (Lee and Lim, 2008), growth hormone-releasing (Lee et al, 2007) and digestionaiding (Jeon et al, 2006) activities. Recent studies revealed that the roots and tuberous roots of Yam contain various bioactive compounds, such as steroidal saponin (Cai et al, 2002), β-sitosterol, antifungal bibenzyls, antifungal phenanthrenes (Coxon et al, 1982;Takasugi et al, 1987), and immune cell-stimulating mucopolysaccharide . Mast cells are one of the most important effector cells in allergic conditions such as asthma, allergic rhinitis, atopic dermatitis, and food allergy (Moon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%